Baseline cardiovascular risk in subjects with type 2 diabetes and chronic kidney disease from the FLOW trial. (3rd October 2022) - Mahaffey, K W; Baeres, F M M; Bakris, G; Bosch-Traberg, H; Gislum, M; Lawson, J; Mann, J F E; Mersebach, H; Perkovic, V; Rossing, P; Tuttle, K; Pratley, R
Abstract: Background: Patients with chronic kidney disease and type 2 diabetes (T2D) have a high risk of progression to kidney failure as well as cardiovascular (CV) events. It is established that glucagon-like peptide-1 receptor agonists (GLP-1RAs) improve glycaemic control and reduce body weight. Some CV outcomes trials have shown that GLP-1RAs reduce CV risk in people with T2D at high CV risk; for example, the SUSTAIN 6 trial demonstrated that the GLP-1RA semaglutide significantly lowered the rate of major CV events (CV death, non-fatal myocardial infarction and non-fatal stroke) versus placebo. Some trials have also indicated that GLP-1RAs reduce albuminuria and estimated glomerular filtration rate (eGFR) decline. Based on these previous results indicating potential kidney-protective effects, the FLOW trial (NCT03819153) is evaluating once-weekly, subcutaneous semaglutide 1.0 mg versus placebo on kidney- and CV-related outcomes in participants with T2D. We describe the baseline characteristics and the calculated CV risk of this patient population using the atherosclerotic CV disease (ASCVD) and second manifestations of arterial disease (SMART) risk calculators. Methods: FLOW is an ongoing, multicentre, randomised, double-blind, parallel-group, event-driven, phase 3b trial, with participants randomised 1:1 to semaglutide or placebo, each in addition to standard of care. Recruitment is complete and 3, 535 participants with T2D, an eGFR ≥25–≤75 mL/min/1.73 m 2, and urine albumin-to-creatinine ratio ≥100–≤5, 000 mg/g have been enrolled. The primary endpoint is time to first occurrence of a kidney composite that includes ≥50% persistent eGFR reduction, kidney failure (persistent eGFR <15 mL/min/1.73 m 2 or initiation of chronic dialysis or kidney transplantation), and kidney-related death, or CV death. Key secondary outcomes include time to first occurrence of CV death, myocardial infarction or stroke. Results: The baseline clinical characteristics and demographics are shown (Table 1). Median age was 68 years, 30% were female, mean diabetes duration was 17 years, and 98% had a history of hypertension. Overall, 52% of participants had a previous CV event. The calculated 10-year risk for ASCVD events in those without prior ASCVD was 31% in males and 18% in females, and in those with previous CV events was 37–56% in males and 35–53% in females depending on the type of CV disease reported in the calculator (Table 2). Conclusions: The FLOW trial has completed enrolment. Based on the ASCVD and SMART risk calculators, the enrolled population has a substantial risk for adverse CV outcomes. Event ascertainment is ongoing, and the FLOW trial will provide evidence for the potential of semaglutide to improve kidney and CV outcomes in the T2D population. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novo Nordisk